2014
DOI: 10.1007/s13204-014-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver and zinc oxide nanoparticles using Pichia fermentans JA2 and their antimicrobial property

Abstract: The development of eco-friendly alternative to chemical synthesis of metal nanoparticles is of great challenge among researchers. The present study aimed to investigate the biological synthesis, characterization, antimicrobial study and synergistic effect of silver and zinc oxide nanoparticles against clinical pathogens using Pichia fermentans JA2. The extracellular biosynthesis of silver and zinc oxide nanoparticles was investigated using Pichia fermentans JA2 isolated from spoiled fruit pulp bought in Vellor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“…The possible reaction mechanism of ZnO formation is the reduction of zinc ion by the phytochemicals such as alkaloids, flavonoids, terpenoids, and tannins present in the plant extract and acts as bioreductant as well as a stabilizing and capping agent to finally produce ZnO nanoparticles. The obtained SPR peak at 375 nm was highly correlated with the previous studies on green synthesis of ZnO NPs [12,16]. The optical band-gap energy was calculated using Tauc's equation (Eq.…”
Section: Uv-vis Analysissupporting
confidence: 80%
“…The possible reaction mechanism of ZnO formation is the reduction of zinc ion by the phytochemicals such as alkaloids, flavonoids, terpenoids, and tannins present in the plant extract and acts as bioreductant as well as a stabilizing and capping agent to finally produce ZnO nanoparticles. The obtained SPR peak at 375 nm was highly correlated with the previous studies on green synthesis of ZnO NPs [12,16]. The optical band-gap energy was calculated using Tauc's equation (Eq.…”
Section: Uv-vis Analysissupporting
confidence: 80%
“…Secondly, the synthesized ZnONPs were capped by these metabolites thereby stabilizing them. In literature, several reports concluded that extracellular synthesis of ZnONPs is a nitrate reductase‐mediated synthesis, which is responsible for the reduction of Zn ions into ZnONPs (Kundu et al ; Chauhan et al ; Kalpana et al ; Gao et al ). The reduction of Zn ions starts through electron transfer from NADH by NADH‐dependent reductase that acts as an electron carrier (Hulkoti and Taranath ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the synthesized ZnONPs exhibited potent antimicrobial activity compared to the standard antimicrobials (amoxicillin/clavulanic acid and nystatin). Previous reports have demonstrated the antimicrobial activity of ZnONPs against several bacterial and fungal species; P. aeruginosa (Jayaseelan et al ; Rajabairavi et al ), Enterococcus sp., S. aureus and P. mirabilis (Chauhan et al ), E.coli and B. subtilis (Balraj et al ), S. aureus and E. coli (Khatami et al ), B. subtilis , E. coli and P. fluorescens (Jiang et al ), H. pylori (Saravanan et al ), A. flavus (Jayaseelan et al ), A. alternata , A. niger , B. cinerea , F. oxysporum and P. expansum (Jamdagni et al ), B. subtilis , S. aureus , E. faecalis , E. coli , P. aeruginosa , K. pneumoniae , C. albicans and C. tropicalis (Abd Elkodous et al ; Gao et al ). Our results further showed that the estimated MIC value of the synthesized ZnONPs against the tested microbes was in the range of 50–100 µg ml −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular biosynthesis of silver and zinc oxide nanoparticles was investigated using Pichia fermentans JA2 by Chauhan et al (2015). The biosynthesized silver nanoparticles were found to inhibit most Gram-negative clinical pathogens used in the study, while zinc oxide nanoparticles only inhibited P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%